Teurgia: quando a Techné encontra Alétheia - Oliveira, Bruno Fiedler de (2021)
Iamblichs of Chalcis (240-325 AD), a neoplatonist philosopher, in his famous work, De Mysteriis, breaks up with the way of thinking of that time by proposing a technique as a more appropriate means to produce the rise of the soul and to reach the Uno, and therefore, to access the purest truth (Aletheia), being a goal for philosophers. The Theurgy, which consisted of a set of ritualistic practices, such as altered states of consciousness, enchantment of statues, sacrifices, invocations, intonation of unintelligible words and so on, is proposed by Jâmblico, as an answer to the questions from his former master, Porphyry. In this dissertation, we will investigate, in the field of The History of Science, the reasons that led him to consider that Theurgy, as a technique, rather than rational intellection (epistemé), would be the best way in the search for salvation and true knowledge. We will seek evidence and elements that corroborate his proposal, under his cosmological view. This dissertation also aims to contribute to the almost non-existent literature about such important character of philosophy in the History of Science